Non-linear relationship between serum α-Klotho and suicide attempt: evidence from a large never-smoking population - Li Zhang; Xin Lin; Lihua Hang (BMC Psychiatry)
Abstract Background Recent study has demonstrated decreased α-Klotho expression in brain regions associated with suicide, including the hippocampus and prefrontal cortex. While serum α-Klotho emerges as a potential mental health biomarker, its relationship with suicidal ideation remains unclear, particularly in never-smokers where smoking’s confounding effects are eliminated. Methods Data from 5,710 lifetime non-smokers were analyzed using the National Health and Nutrition Examination Survey (NHANES) were analyzed, with smoking status verified through detailed questionnaires. Multiple logistic regression models were employed to examine the association between serum α-Klotho and suicidal ideation. Generalized additive models and threshold effect analyses were conducted to explore non-linear relationships, with further stratification by gender and hypertension status. Results The mean serum α-Klotho levels across quartiles (Q1-Q4) were 557.50 ± 88.46, 747.74 ± 43.71, 914.48 ± 55.51, and 1286.64 ± 278.54 pg/mL, respectively. Initial analyses showed no linear association between serum α-Klotho and suicidal ideation. However, threshold effect analysis identified an inflection point at 1088.8 pg/mL, above which increased α-Klotho levels were associated with reduced suicide risk (OR = 0.998, 95% CI: 0.996-1.000, P = 0.040). Gender-specific analyses revealed a significant protective effect in females above 735.2 pg/mL (OR = 0.999, 95% CI: 0.998-1.000, P = 0.031). Among hypertensive participants, a threshold at 713.1 pg/mL demonstrated increased risk below (OR = 1.004, 95% CI: 1.000-1.007, P = 0.026) and protective effects above (OR = 0.999, 95% CI: 0.998-1.000, P = 0.042). Conclusions This study provides novel evidence from a non-smoking population, demonstrating that serum α-Klotho exhibits a non-linear relationship with suicidal ideation, with protective effects observed above specific thresholds.